Evaluation of the Relationship Between Preferential Looking Testing and Visual Evoked Potentials as a Biomarker of Cerebral Visual Impairment - Raja, Sruti; Emadi, Batool Sahar; Gaier, Eric D.; Gise, Ryan A.; Fulton, Anne B.; Heidary, Gena (Frontiers in Human Neuroscience, 2021)
Cerebral visual impairment (CVI) is a leading cause of visual impairment in children in developed countries, but diagnostic tools to detect CVI are limited. We sought to analyze the visual acuity of children with CVI as assessed by visually evoked potentials (VEP) and preferential looking test (PLT) to determine whether the relationship between the visual outcomes on these two testing methods may serve as a biomarker of CVI. We performed a retrospective chart review of patients with a confirmed diagnosis of CVI and at least one ophthalmological assessment with visual acuity measured by VEP and PLT. Of the 218 patients included in the study, the most common condition associated with CVI was an underlying genetic disorder (36%, 79/218). Treatment for seizures occurred in the majority of the entire cohort of patients (80%, 175/218). Ophthalmic comorbidities included retinal disease in 23 patients, optic nerve disease in 68 patients, nystagmus in 78 patients, and strabismus in 176 patients. When assessed by either VEP or PLT, visual acuity in children with CVI fell below expected norms. At initial and final presentations, VEP acuity exceeded PLT acuity by one or more octaves, and this difference was greater than expected compared with normal visual development. We propose utilizing this quantifiable disparity between VEP and PLT as a biomarker of CVI.